Assessing the quality of potentially reclaimed mine soils: Environmental implications for the construction of a nearby water reservoir. (February 2019) - Cánovas, Carlos Ruiz; Caro-Moreno, David; Jiménez-Cantizano, Francisco A.; Macías, Francisco; Pérez-López, Rafael
Abstract: The cementation complex of Las Viñas (SW Spain) is a partially reclaimed abandoned mine site located in the drainage basin of a water reservoir currently under construction. The aim of this investigation was to analyze these mine soils to evaluate their potential environmental impact, especially on the final reservoir water quality. Results evidence the extremely high acidity of soils (pH of 3.4 and maximum potential acidity of 47 kg CaCO3 /ton), with high concentrations of trace elements, especially As, Pb and Cu. Sequential extraction data reveal the potential release of significant quantities of Mn, Cd, Cu and other easily-soluble trace elements by rainfalls. The weathering and transport of soils to the bottom sediments of the planned reservoir could lead to the release of significant quantities of toxic trace elements to the water column if anoxic (mainly As, Sb, Cr, Ni, Cu and Pb) or oxic (mainly Hg, Pb, V, Cu and As) conditions are found in the sediments. The acidity and metals released from these soils could jeopardize the quality of the reservoir waters. Remediation measures must be therefore adopted, focused on the cleanup and liming of soils in order to promote colonization and vegetation succession, thus avoiding soil erosion and limiting metal release to the hydrosphere. This study proposes the use of different low-cost materials to improve the soil quality, limiting the metal transfer to the planned reservoir water. The information contained in this study could be of great importance in other watersheds affected by abandoned mine sites. Graphical abstract: Highlights: Soils affected by mining exhibit an acidic nature and high metal concentrations. Eroded materials may be deposited in the bottom sediments of a planned water reservoir. This study evidences a high potential metal/loid release from soils to the reservoir water column. Different low-cost materials are proposed to limit the metal/loid transfer.